SOCIAL ENGINEERING: CRISIS IN HUMANITY - Kevin Tjendrawinata (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Digital development in Indonesia have had a significant impact and contribution, both positive and negative. When misused, various kinds of crimes in the cyber world (cybercrime) begin to emerge, one of which is Social Engineering techniques. Using previous studies as references, it can be concluded that Social Engineering is a technique of attacking through social mechanisms or human interaction (persuasions, influences, and other interactions), aiming to control the actions of victims, both consciously and unconsciously. Due to the nature of the Social Engineering case is user negligence, not all companies have compensation policy for losses. On the other hand, users/consumers feel aggrieved due to the "gaps" that can be exploited by fraudsters. As a result, the company's public image shall reduced or even vanish upon their eyes. This research’s purpose is to explore Social Engineering cases, starting from the definition, mechanism, previous Social Engineering cases, along with the behavior of the Indonesian people regarding cyber security by distributing e-questionnaires. Keywords: social engineering, cybersecurity, cyberattack, fraud prevention